Czynniki sukcesu małych przedsiębiorstw - Jakubów, Leon; Sołoducho-Pelc, Letycja (The Success Factors of Small Firms, 2006)
The aim of this article is to present the specific success factors of small business. The main reason for the small firms success is a managerial competence of entrepreneur and the a leadership style. Another important factors are: "good team" and employee skills, modem management style, permanent development and client-orientation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 274-279